Effects of Formalin Fixation on Trace Element Concentrations in Bottlenose Dolphin (Tursiops truncatus) Tissues. (22nd May 2020) - McCormack, Meaghan A.; Jackson, Brian P.; Dutton, Jessica
Abstract: Odontocetes are considered ideal sentinel species to monitor environmental trace element concentrations. Although frozen tissues are preferable for trace element analysis, formalin‐fixed tissues are often the only samples available; however, it is uncertain whether formalin fixation alters tissue trace element concentrations. To explore whether formalin‐fixed tissues could be utilized for toxicology studies, concentrations of 14 trace elements (arsenic [As], cadmium, cobalt, chromium, copper, iron, mercury, manganese, nickel, lead, selenium, tin, vanadium, and zinc [Zn]) were measured in frozen and formalin‐fixed bottlenose dolphin ( Tursiops truncatus) tissues following short‐term (6 wk; tissues: blubber, liver, and lung) and long‐term preservation (3–7 yr; tissues: blubber, brain, kidney, liver, lung, and skin) using inductively coupled plasma mass spectrometry. Following both short‐term and long‐term preservation, there were significant differences in tissue trace element concentrations between preservation methods. Some trace elements were found in greater concentrations in frozen tissues compared with formalin‐fixed tissues, suggesting leaching (e.g., mean As concentrations were between 1.4 and 7.6 times greater in frozen tissues). In contrast, other trace elements were found in greater concentrations in formalin‐fixed tissues compared with frozen tissues, suggesting contamination (e.g., mean Zn concentrations were up to 8.7 times higher in some formalin‐fixed tissues). Our results suggest that it may be possible to account for the effects of formalin fixation for some trace elements, but leaching and contamination should be carefully considered. Environ Toxicol Chem 2020;39:1149–1164. © 2020 SETAC